PENGARUH KEDISIPLINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA DINAS KESEHATAN KABUPATEN KUTAI BARAT DI SENDAWAR - Mukhtar Hidayat (LPPM University 17 Agustus 1945 Samarinda, 2019)
The purpose of this paper is to determine the significant effect of discipline and motivation variables together on the performance of employees at the West Kutai District Health Office at Sendawar. And also to find out the discipline and motivation which is the dominant influence on employee performance at the West Kutai District Health Office at Sendawar. While the usefulness of writing is to provide information about discipline and motivation that can affect the performance of employees who can help leaders take policies to try to improve discipline and motivation so that there is an increase in employee performance and at the same time the performance of the Kutai Barat District Health Office at Sendawar itself.The correlation coefficient (R) is 0.9090 which means that the discipline and motivation variables together have a direct or positive relationship with the performance of employees at the West Kutai District Health Office at Sendawar. The value of R Squared (R2) is 0.8260 or 82.60%, which means that the performance of employees at the West Kutai District Health Office at Sendawar can be determined by the variables of discipline and motivation. In other words, the contribution of discipline and employee motivation to the performance of employees at the Kutai Barat District Health Office at Sendawar was 82.60%. While the remaining 17.40% is determined by other variables outside of this study.While the influence of each variable, namely the discipline variable (X1) has an effect on employee performance of 56.20%, while the motivation variable (X2) has an effect on employee performance by 65.00%. So that it can be said that motivation is a variable that has a greater influence on the performance of employees at the West Kutai District Health Office at Sendawar. The first good hypothesis test can be accepted because F count is 135,145 and F table 3,170 which means F count> F table. Likewise, the second hypothesis can be accepted because it is proven that the influence motivation is greater on the performance of employees at the West Kutai District Health Office at Sendawar